Al-Bukhari's chapter on predestination: a critical evaluation - Khan, Israr Ahmad (IIUM Press, 2009)
One of the chapters in the Sahih of al-Bukhari (d.256 A.H.) is “Kitab al-Qadar” (Chapter on Predestination). It contains twenty seven (27) traditions. The message conveyed through these reports is that the human life is preordained in all its detail. A critical examination of all these Ahadith shows that despite their authenticity from the angle of the chain (sanad), their text (matn) may not withstand principled scrutiny. The interpretation of these traditions advanced by several commentators of al-Bukhari’s Hadith works, such as al-Tibi (d.743 A.H.), al-Kirmani (d.786 A.H.), Ibn Hajar (d852 A.H.), al-‘Ayni (d.855 A.H.), al-Qastalani (d.923 A.H.), al-Sindi (d.1138 A.H.), etc., is essentially chain-focused and non text-focused. At times, these scholars do pay attention to some of the said traditions from the angle of the text (Matn) but remain short of applying universal principles of Hadith interpretation. Scholars of Hadith Studies have set five criteria to interpret the text of Hadith: (1) the Qur’an, (2) the highly authentic Ahadith, (3) the sound reason, (4) the established history, and (5) the moderation. In the present research these principles have been applied to check and interpret the text of all the twenty seven traditions of al-Bukhari’s chapter on predestination.